Comparative Analysis of Alternative Fuels Used in Road Transport - Jan Lizbetin; Ladislav Bartuska; Aleksandr Rakhmangulov (Communications - Scientific letters of the University of Zilina, 2017)
In recent years, especially alternative fuels have been undergoing significant and rapid development, since the society is aware of the negative impacts of a long term and excessive use of fossil fuels on the environment as well as of the fact that the raw materials are finite. The article shows a new approach to using of alternative fuels in transport in the future. The description introduces both conventional and unconventional fuels. The analysis is focused on the comparison of the fuels in terms of the formation of CO, SO2, NOx and CO2 emissions, as well as their energy performance. In the conclusion the paper outlines the future of automobile propulsion in the context of sustainable development of transport.